Esensialitas Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru Sekolah Dasar (Studi Kasus di SDN 216 Sondariah) - Suharyanto H. Soro; Nenden Kurniati; Robian Henri; Nevi Nasyanawati (LP. Ma'arif Janggan Magetan, 2024)
Teacher discipline is a key factor in creating a conducive educational environment and supporting effective learning at schools. Although most teachers have demonstrated good discipline, some still face challenges in time management and fulfilling administrative responsibilities. This study aims to analyze the essenciality of school leadership in increasing teacher discipline. The research method employed is qualitative with an approach of case study, with data collected through in-depth interviews, observations, and document analysis. The results of the research indicated that the school principal plays roles as a leader, educator, and motivator, through clear disciplinary policies, time management training, and the creation of a positive work environment. Strategies such as providing constructive feedback, rewards, and regular coaching have proven effective in enhancing and increasing teacher discipline. The study concludes that the role of school leadership is critical in establishing a strong culture of discipline, which ultimately has a positive impact on the quality of learning and the achievement of educational objectives in schools.